Legal Policy of the Establishment of Deputy Attorney General for Military Affairs in the Structure of the Attorney General's Office of the Republic of Indonesia - Raihany, Farras Audia; Zurnetti, Aria; Elda, Edita (Nagari Law Review, 2024)
The legal challenges within Indonesia's justice system revolve around the absence of a unified implementation of the one-roof prosecution policy for military crimes. Despite the apparent coordination authority vested in the Attorney General, as highlighted in Article 57 of the Military Justice Law and Article 18 of the Amendments to the Prosecutor's Office Law, practical enforcement reveals a lack of reporting by Auditors to the Attorney General regarding the prosecution of military criminal cases. Furthermore, issues arise in handling connection cases, where the Criminal Procedure Code stipulates joint trials for handling perpetrators from both general and military justice systems. However, in practice, many connectivity cases are tried separately, leading to dualism and disparities of prosecution. In response, a suggested solution was to establish the Deputy Attorney General for Military Affairs (DAGMA) as the new structure within the Attorney General's Office. This paper aims to obtain a comprehensive explanation regarding the legal policy behind establishing DAGMA as the assistant of the Attorney General in handling military affairs and connectivity cases. The method used in this research is juridical-normative, which mainly focuses on examining the law as norms or rules that apply in society and serve as guidelines for individual behavior. The findings proved that establishing DAGMA is the Government's effort to implement legal reform, especially regarding optimizing the performance of the Indonesian Prosecutor's Office as the implementer of state prosecutorial power to realize prosecutorial unity in Indonesia.